MBCL-38. MEDULLOBLASTOMAS ASSOCIATED WITH APC GERMLINE MUTATION: A MULTICENTRIC FRENCH AND BELGIAN REVIEW. Issue 2 (22nd June 2018) - Surun, Aurore; Brugières, Laurence; Guerrini-Rousseau, Léa; Varlet, Pascale; Lacour, Brigitte; Faure-Conter, Cécile; Leblond, Pierre; Bertozzi-Salomon, Anne-Isabelle; Berger, Claire; Andre, Nicolas; Sariban, Eric; Prieur, Fabienne; et al.
Abstract: Medulloblastoma may occur in a context of APC germline mutation and familial adenomatous polyposis. We aimed to describe clinical features of patients with medulloblastoma occurring in this context. We performed a multicentric retrospective review of French and Belgian patients treated for medulloblastoma with identified or highly suspected (personal or familial history) APC germline mutation. Genetic status, clinical and histological characteristics, treatments and outcome were reported. Eleven patients with known or suspected APC germline mutation, mostly on exon 15 (N=6/9 available data), were diagnosed with medulloblastoma at a median age of 10.6 years [6-32]. Medulloblastomas were mainly non-metastatic (N=9/11), classic (N=9/9 available data, central review ongoing), with no significant residual tumor after surgery (N=9/11). All patients underwent radiotherapy (median craniospinal dose: 35 Gy), combined with chemotherapy for 10 patients. No relapse was noticed (median follow-up: 11 years). Secondary tumors (N=8) occurred in 7 patients, including 1 lethal malignant Triton tumor in the irradiation field, 1 thyroid carcinoma, and 6 desmoid tumors (5 abdominal tumors, 1 occipital tumor in the irradiation field). Pre-symptomatic polyposis was diagnosed for 9 patients at a median age of 15.5 years, prior to medulloblastoma for 2 of them. Medulloblastomas associated with APC germline mutation have favorable clinical outcome, even for metastatic tumors, with no relapse in this small series of patients, in line with WNT-medulloblastomas' profile. Yet, long-term survival is clouded by second tumor occurrence, with potential radiation-induced tumors. These findings raise the question of applying de-escalation therapeutic protocol for these patients with reduced intensity craniospinal irradiation.